Putting it together how Stephen Sondheim and I created Sunday in the park with George - Lapine, James 1949- (Farrar, Straus and Giroux, 2021)
"A behind-the-scenes look at the making of the iconic Broadway musical Sunday in the Park with George"--
Keywords: Sondheim, Stephen -- 1930-2021 -- Sunday in the park with George; Geschichte; Entstehung; Sondheim, Stephen / Sunday in the park with George; Lapine, James / Sunday in the park with George; Musicals / Production and direction / New York (State) / New York; Sunday in the park with George (Sondheim, Stephen); Musicals / Production and direction; New York (State) / New York; Erlebnisbericht